Peningkatan Kualitas Keilmuan melalui Pelatihan Mengkafani Jenazah terhadap Masyarakat Griya Kembang Putih Guwosari - Rohmansyah, Rohmansyah; Catur Ilham Wicaksono Gunawan (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2026)
The Griya Kembang Putih (GKP) community faces a challenge in properly performing the shrouding procedure for corpses, as they lack the skills required to follow Islamic law. They have traditionally followed customs passed down by local community leaders without understanding their authenticity. To address this issue, a rukti (corpse care) service has been initiated, focusing on educating the GKP community about the correct shrouding process based on the Prophet's guidance. The service employs a combination of lectures and hands-on methods to deliver knowledge. The outcome of this service is that the community now understands the proper shrouding procedure, although ongoing learning is still needed. They are now equipped to differentiate between the traditional practices they once followed and the practices that align with Islamic teachings as conveyed by the Prophet Muhammad SAW. The shrouding procedure is presented step by step, making it easier for the community to comprehend and apply the correct methods when handling a deceased individual. The procedure begins by setting up a table for the body, placing seven cloth ropes, and preparing three pieces of shroud for men and five pieces for women. The body is then placed on the shroud, which is folded from right to left and left to right, with ropes tied around each part of the covered body. As a result, the GKP community is now capable of independently performing shrouding procedures in line with Shari'a law, guided by the Prophet's teachings, rather than adhering to ancestral customs.